Metody i techniki oceny poziomu jakości w sferze usług turystycznych - Jaremen, Daria E. (Methods and Techniqes for Quality Level Assessment in the Sector of Tourism Sevices, 2008)
The assessment of services quality becomes on one hand the basis for improving their level and on the other poses numerous difficulties. It requires, among others, the application of proper, standardized research methods. However, any tourism enterprise which aims at the improvement of the provided services quality should perform its measurement by means of objective methods application. The article presents three selected methods which are the most useful in tourism sector and also the most frequently applied in practice. Among them are SERVQUAL, SERVPERF, and importance-performance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 133-144